Comparative Effectiveness of Biofertilizer and EM4 in Organic Waste Biodegradation in Soil - Fasya Nurul Fachriah; Anisa Ramadani; Dinar Febbyana; Hijrah Nurkholifah; Farhah Auliya; Jherty Sinaga; Amalianneisha Rafadewi Andhanatami Putri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The increasing accumulation of household organic waste poses serious environmental challenges due to inadequate management practices. Biological degradation using microbial activators is considered an effective and environmentally friendly approach to accelerate organic waste decomposition. This study aimed to analyze the effectiveness of biofertilizer and Effective Microorganisms-4 (EM4) in enhancing the biodegradation of household organic waste in soil media. The research employed a simple experimental method with three treatments: control without activator, addition of biofertilizer, and addition of EM4. Organic waste was layered with soil and incubated for four weeks, with periodic observations of physical changes, including aroma, color, waste condition, and residual decomposition. The results showed that EM4 treatment exhibited the most effective biodegradation, characterized by reduced waste residue, brownish-black color, and an earthy aroma. Biofertilizer enhanced biodegradation relative to the control, though the process proceeded more gradually due to microbial adaptation. In contrast, the control treatment demonstrated the slowest degradation rate. In conclusion, the application of microbial activators, particularly EM4, significantly enhances the biodegradation of organic waste in soil media. It is recommended that EM4 be utilized as an alternative, eco-friendly strategy for household organic waste management, with attention to environmental factors such as temperature, pH, and moisture to optimize microbial activity.